Effect of temperature on wet agglomeration of crystals - Maghsoodi, Maryam (Mashhad University of Medical Sciences, 2014)
OBJECTIVE(S): This study dealt with the wet agglomeration process in which a small quantity of binder liquid was added into a suspension of crystals, directly in the stirring vessel where the crystallization took place. The purpose of this investigation was evaluation of the effect of temperature on the agglomeration process in order to gain insight into the mechanism of the formation of the agglomerates. MATERIALS AND METHODS: Carbamazepine was used as a model drug and water/ethanol and isopropyl acetate were used as crystallization system and binder liquid, respectively. The agglomeration of crystals was carried out at various temperatures and the agglomerates were characterized in terms of size, morphology, density and mechanical strength. RESULTS: Evaluation of the agglomerates along the course of agglomeration shows that the properties of the particles change gradually but substantially. Higher temperature of the system during agglomeration process favors the formation of more regular agglomerates with mechanically stronger and denser structure; this can be explained by the promotion effect of temperature on the agglomeration process. CONCLUSION: With optimized wet agglomeration temperature, spherical, dense, and strong agglomerates can be obtained.